Influence of motivation on organizational commitment. Case study of Ratchaburi Provincial Administrative Organization - U- THAIRATANA , Pichaya; RITTIBOONCHAI , Wisit; INTHAVICHIT , Lathtana; PUKLORD , Pipat; DETCHIT, Sangdaw (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
The purposes of this research are to 1. Study of organizational commitment: a case study of Ratchaburi Provincial Administrative Organization When classified by personal factors; and 2. Studying the influence of motivation on organizational commitment. Case study of Ratchaburi Provincial Administrative Organization. Researchers collected a sample of 138 people using a simple random sampling method. The statistics used in data analysis consisted of percentage, mean, standard deviation, t-test, one-way analysis of variance, and multiple regression analysis. The research results showed that: 1. Organizational commitment: The case study of the Ratchaburi Provincial Administrative Organization was different according to age, education, work age, and salary. 2. Influence of motivation on organizational commitment, case study Ratchaburi Provincial Administrative Organization can be composed with Physical needs and The need for praise. The multiple regression analysis equations is; organizational commitment (Y) = 1.60 + 0.25. Physical needs (X1) ** + 0.07 The need for safety and stability (X2) + 0. 09 Acceptance requirement (X3) + 0. 29 The need for praise (X4) **+ 0. 04 The need for success in life (X5) With the prediction accuracy of the said equation at 59 percent.